Sequential C−H Borylation and N‐Demethylation of 1, 1′‐Biphenylamines: Alternative Route to Polycyclic BN‐Heteroarenes. (17th April 2019) - Zhang, Jianbo; Jung, Hoimin; Kim, Dongwook; Park, Sehoon; Chang, Sukbok
Abstract: Described herein is an unprecedented access to BN‐polyaromatic compounds from 1, 1′‐biphenylamines by sequential borane‐mediated C(sp 2 )−H borylation and intramolecular N‐demethylation. The conveniently in situ generated Piers' borane from a borinic acid reacts with a series of N, N ‐dimethyl‐1, 1′‐biphenyl‐2‐amines in the presence of PhSiH3 to afford six‐membered amine‐borane adducts bearing a C(sp 2 )−B bond at the C2′‐position. These species undergo an intramolecular N‐demethylation with a B(C6 F5 )3 catalyst to provide BN‐isosteres of polyaromatics. According to computational studies, a stepwise ionic pathway is suggested. Photophysical characters of the resultant BN‐heteroarenes shown them to be distinctive from those of all‐carbon analogues. Abstract : Über zwei Stufen verläuft eine boranvermittelte C‐H‐Borylierung und N‐Demethylierung von Biphenylaminen unter Bildung neuartiger BN‐Heteroarene mit charakteristischen photophysikalischen Eigenschaften. Die intramolekulare N‐Demethylierung der Boran‐Amin‐Zwischenstufen wird durch einen B(C6 F5 )3 ‐Katalysator vermittelt, benötigt allerdings hohe Temperaturen. Das Verfahren zeichnet sich durch übergangsmetallfreie Bedingungen aus und setzt harmlose Nebenprodukte (H2 und CH4 ) über einen mechanistisch faszinierenden ionischen Reaktionsweg frei.